A new species of Ilex L. (Aquifoliaceae) from the northestern part of the State of Queretaro, Mexico - Carranza González, Eleazar (Instituto de Ecología, A.C., 2004)
Ilex servinii (Aquifoliaceae) a new species from the northeastern portions of the state of Queretaro, Mexico, is described and illustrated. This tree presents wider leaves than the other species of central Mexico, its flowers are bigger and it is practically glabrous. It occurs in oak-pine forest and cloud forest. The species is very rare. A comparison is made between Ilex servinii and I. tolucana Hemsl., I. discolor Hemsl., I. brandegeana Loes., three other species from central Mexico.